The Role of Affiliators in Increasing Brand Awareness in the Digital Era - Sulaiman, Maliah (Management Department Universitas Islam Negeri Sumatera Utara, 2024)
The advancement of digital technology has transformed how companies cultivate brand awareness, highlighting effective and quantifiable techniques via affiliate marketing. Affiliators, as external collaborators, are crucial in broadening market access and fostering consumer engagement. This study seeks to examine the function of affiliates in enhancing brand awareness in the digital age, concentrating on strategy and efficacy. A descriptive qualitative approach was employed to collect data through a literature review, examining affiliate practices on platforms like TikTok and Shopee. The findings indicate that affiliates, by leveraging personal relationships and innovative material, markedly enhance brand visibility and credibility. These findings underscore the significance of the AIDA principle (Attention, Interest, Desire, Action) in affiliate marketing, which effectively enhances consumer engagement and buy intention. Moreover, affiliate programmes enhance brand credibility and sales efficacy. Notable instances encompass the TikTok Affiliate and Shopee programmes, which exemplify the efficacy of affiliate marketing in the digital realm. The research finds that a transparent and smart affiliate approach can enhance brand recognition and generate economic opportunities for affiliates.Keywords: Affiliate, Brand Awareness, Digital Marketing, Tiktok, Shopee